Emas Hijau dan Biru dari Jerowaru: Mengangkat Ekonomi Warga Pesisir Melalui Rumput Laut dan Lobster - Yazid Syahram; Haekal Hakim (Journal of Community Development and Empowerment, 2026)
Jerowaru District, located in East Lombok Regency, possesses extraordinary marine potential, particularly in the development of superior commodities such as seaweed, nicknamed "green gold," and lobster, known as "blue gold." Despite this abundant natural potential, coastal communities in this area generally face classic obstacles, including a low understanding of modern cultivation technology capacity, a lack of post-harvest processed product diversification, and a high dependence on middleman market chain systems. This community service activity aims to improve the economic welfare of coastal residents in Jerowaru through strategies to optimize the sustainable management of seaweed and lobster cultivation. The implementation method used in this service program is based on Participatory Action Research (PAR), which encompasses three main stages: training in modern environmentally friendly cultivation techniques, assistance in diversifying processed seaweed products into high economic value commodities, and education on group financial management alongside the expansion of digital-based market access. The results of this community service activity show a significant increase in the technical skills of cultivators, a 45% increase in the economic added value of products through processing innovation, and the formation of a much more independent joint business group institution. Through this integrated capacity-building program, fishermen's dependence on middlemen can be gradually reduced due to the opening of direct market access networks to consumers and industries. In conclusion, the synergistic utilization of the potential of "green gold" and "blue gold" managed in a modern way can serve as the main pillar in boosting the domestic income of fishermen's families, creating new job opportunities, and achieving economic independence for the Jerowaru coastal community.